Expediente - GEOGRAPHIA OPPORTUNO TEMPORE - Vol. 7 nº2 - 2021 - Fraga, Nilson Cesar (Geographia Opportuno Tempore, 2021)
GEOGRAPHIA OPPORTUNO TEMPORE ISSN: 2358-1972 Geographia Opportuno Tempore, V. 7, Nº. 2, 2021.